Water electrolysis oxygen evolution composite catalytic electrode and preparation method and device thereof
By adding a composite coating of porous nickel matrix and nanoporous polymer ceramic powder on the nickel-iron-based oxygen evolution anode, the problem of catalytic layer falling off under high current density is solved, and high efficiency and low cost of electrolyzing hydrogen production is achieved.
Patent Information
- Application Number
- CN202510210183.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-05-02
AI Technical Summary
The existing nickel-iron-based oxygen evolution anode has insufficient electrochemical stability when operating at high current density, resulting in the catalytic layer falling off and affecting the efficiency and cost of hydrogen production in electrolytic water.
A porous nickel matrix is used as the substrate, and a nickel-iron-based hydroxide catalyst and a nanoporous polymer ceramic powder composite coating are supported to form a stable composite catalytic electrode.
The structural stability and operational stability of the electrolytic oxygen-analyzed composite catalytic electrode are improved, and the energy consumption and cost of electrolyzed hydrogen production are reduced.
Smart Images

Figure CN119913562A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a composite catalytic electrode for oxygen evolution by electrolysis of water and a preparation method and device thereof. Background Art
[0002] Hydrogen has the advantages of high energy density and environmental friendliness, and is an ideal choice to replace fossil energy. As a highly efficient and clean energy with development prospects, the current industrial hydrogen production is mainly restricted by environmentally unfriendly production methods such as coal-to-hydrogen production that consumes fossil energy; in contrast, the use of green electricity to produce hydrogen through water electrolysis is not only clean and environmentally friendly, but also produces high-purity hydrogen, and is expected to become the next generation of large-scale industrial hydrogen production methods.
[0003] Hydrogen production by water electrolysis can convert green electricity such as hydropower, wind power, and photovoltaic power into chemical energy and store it in hydrogen to further prepare green chemicals. The current commercial alkaline water electrolysis hydrogen production mainly uses nickel-based catalytic electrodes, PPS cloth or composite diaphragm, KOH electrolyte with a concentration of ~30wt%, and applies a certain cell pressure to electrolyze water to produce hydrogen under working conditions of 80-90℃. The widely used nickel mesh oxygen evolution catalytic electrode mainly works at low current density, and its intrinsic water electrolysis catalytic activity is not ideal, resulting in a large overpotential during the electrolysis process, which increases the energy consumption of electrolysis and causes the cost of water electrolysis hydrogen production to be too high. Therefore, there is an urgent need for water electrolysis oxygen evolution catalytic materials with high catalytic activity to reduce the cost of hydrogen production. Among them, iridium oxide oxygen evolution electrode has strong catalytic ability and good corrosion resistance, but it is expensive. Therefore, nickel-iron-based oxygen evolution catalytic electrode with good oxygen evolution activity and low price is an ideal choice for large-scale water electrolysis hydrogen production. The NiVIr oxygen evolution anode prepared in the literature (Nature Communications, 2019, 10, 3899) can be used at 200 mA / cm 2 The NiFeMo oxygen evolution anode prepared in the literature (Nature Communications, 2022, 13, 219) operated for more than 400 hours at a current density of 100 mA / cm 2 The electrolysis voltage is only 1.728 V at the current density. The iron-cobalt alloy particle / nickel hydroxide / nickel mesh composite electrode prepared by the in-situ growth method in patent CN112501645B can be 2 The patent CN115478290A uses a synthetic NiFe-LDH nickel-based oxygen evolution electrode and a commercial foamed nickel-molybdenum alloy hydrogen evolution electrode. The electrolytic cell test shows that the current density reaches 700mA / cm at a 2V electrolysis voltage. 2 .
[0004] However, the electrochemical stability of the nickel-iron-based oxygen evolution anode needs to be further improved, especially when operating at high current density. Therefore, improving the electrochemical stability of the oxygen evolution anode under high current density conditions has become a problem that needs to be solved urgently. The existing technology usually uses electrochemical deposition or in-situ growth method to prepare nickel-iron-based oxygen evolution catalytic electrodes, which often have the problem of poor adhesion between the catalytic layer and the substrate, affecting the stability of the catalytic electrode. Especially when operating at high current density, the oxygen evolution catalytic layer is more likely to fall off. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a composite catalytic electrode for oxygen evolution by electrolysis of water and a preparation method and device thereof in order to address the above-mentioned problems existing in the prior art, so as to enable efficient and low-cost preparation of a non-precious metal composite catalytic electrode for oxygen evolution, and the composite catalytic electrode has a low oxygen evolution potential and high electrolysis operation stability, and can meet the application requirements of industrial high current density electrolysis of water.
[0006] According to a first aspect of an embodiment of the present invention, there is provided a composite catalytic electrode for electrolyzing water and evolving oxygen, comprising: A porous nickel substrate, a composite catalyst layer and a porous composite bonding layer; The composite catalyst layer is loaded on the porous nickel substrate, and the porous composite bonding layer is coated on the surface of the composite catalyst layer; The composite catalyst layer comprises a nickel-iron-based hydroxide catalyst, and the porous composite bonding layer is a nano-porous polymer ceramic powder composite coating.
[0007] Preferably, the composite catalyst layer further comprises a catalyst promoter of molybdenum, vanadium, manganese or cobalt; The polymer in the nanoporous polymer ceramic powder composite coating is one or more of the alkali-resistant polymers polysulfone or polyethersulfone; The ceramic powder in the nanoporous polymer ceramic powder composite coating is one or more of zirconium oxide, titanium oxide, cerium oxide and niobium oxide.
[0008] Preferably, the total loading of the nickel-iron-based hydroxide catalyst is 0.1-30 mg / cm 2 , the nickel-iron molar ratio is 1:50-2:1; The loading amount of the nanoporous polymer ceramic powder composite coating is 0.01-5 mg / cm 2 The mass ratio of polymer to ceramic powder is 100:1-1:20.
[0009] Preferably, the total loading of the nickel-iron-based hydroxide catalyst is 0.5-30 mg / cm 2 , the nickel-iron molar ratio is 1:4-1:1; The loading amount of the nanoporous polymer ceramic powder composite coating is 0.1-4 mg / cm 2 The mass ratio of polymer to ceramic powder is 100:1-1:20.
[0010] Preferably, the porous nickel substrate is a nickel mesh, a nickel felt, a nickel alloy mesh, a nickel foam or a nickel alloy foam.
[0011] According to a second aspect of the present invention, a method for preparing a composite catalytic electrode for oxygen evolution by electrolysis of water is provided, characterized in that it comprises: adding a stabilizer to a nickel-iron catalyst precursor compound solution to form a catalyst solution; After coating the catalyst solution on the surface of the porous nickel substrate, the catalyst solution is reacted with an alkaline solution to form a composite catalyst layer; After coating the ceramic powder and the polymer slurry onto the surface of the composite catalyst layer, a protective layer is formed by a phase transfer method.
[0012] Preferably, in the method for preparing the composite catalytic electrode for oxygen evolution by water electrolysis, the stabilizer is amino acid, hydrochloric acid, sulfuric acid, acetic acid, nitric acid or citric acid; The iron precursor salt in the nickel-iron catalyst precursor compound solution is one or more of ferric chloride, ferric nitrate, ferric sulfate, and ferric acetate; The nickel precursor salt in the nickel-iron catalyst precursor compound solution is one or more of nickel chloride, nickel nitrate, nickel sulfate, and nickel acetate; In the nickel-iron catalyst precursor compound solution, the molar ratio of the nickel-iron precursor to the stabilizer is 1:2-50:1.
[0013] Preferably, after coating the catalyst solution onto the surface of the porous nickel substrate, the method further comprises: The porous nickel substrate coated with the catalyst solution is dried and then reacted in situ with an alkaline solution to form a composite catalyst layer.
[0014] Preferably, in the method for preparing the composite catalytic electrode for oxygen evolution by electrolysis of water, The ceramic powder in the ceramic powder and polymer slurry is an oxide or a composite oxide of a metal chemical element; The ceramic powder and the polymer in the polymer slurry are alkali-resistant polymers; The slurry solvent in the ceramic powder and polymer slurry is a solution capable of dissolving the alkali-resistant polymer.
[0015] According to a third aspect of the present invention, a water electrolysis hydrogen evolution device is provided, wherein the electrode of the water electrolysis hydrogen evolution device is any one of the above-mentioned water electrolysis oxygen evolution composite catalytic electrodes.
[0016] The technical solution provided by the embodiments of the present invention may have the following beneficial effects: It can be understood that the catalyst layer of the composite catalytic electrode for oxygen evolution by electrolysis of water shown in the present invention is coated with a porous composite coating. Since a porous structure is formed on the surface of the Ni mesh substrate, the composite catalytic layer can be combined with the metal substrate to form a stable structure, and the porous ceramic polymer composite coating can stably cover the surface of the composite catalytic layer, so that the composite catalytic electrode exhibits high long-term structural stability. At the same time, the prepared composite catalytic electrode for oxygen evolution by electrolysis of water exhibits long-term operating stability when operating at a high current density, and has important industrial application value.
[0017] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0019] Figure 1 It is a schematic diagram of the preparation process of the oxygen evolution composite catalytic electrode; Figure 2 The Fe prepared in Example 1 3+ / Fe 2+ / Ni 2+ (OH) x @PES / ZrO 2 -1 SEM image of catalytic electrode; Figure 3 is a SEM image of the porous Ni mesh prepared in Comparative Example 1; Figure 4 Fe prepared in Comparative Example 2 3+ / Fe 2+ / Ni 2+ (OH) x SEM image of catalytic electrode; Figure 5 This is the SEM image of the Ni mesh prepared by acid etching without ultrasonic treatment; Figure 6 1 is a graph showing the variation of electrolysis voltage of oxygen evolution catalytic electrodes prepared in Example 1, Comparative Example 1 and Comparative Example 2 with current density; Figure 7 1 is a graph showing the variation of electrolysis voltage of oxygen evolution catalytic electrodes prepared in Example 1, Comparative Example 1 and Comparative Example 2 with electrolysis time; Figure 8 Fe prepared in Comparative Example 2 3+ / Fe 2+ / Ni 2+ (OH) xSEM image of the catalytic electrode after testing; Fig. 9 The Fe prepared in Example 1 3+ / Fe 2+ / Ni 2+ (OH) x @PES / ZrO 2 -1SEM image of catalytic electrode after testing; Fig.10 The Fe prepared in Example 2 3+ / Fe 2+ / Ni 2+ (OH) x @PES / ZrO 2 -2 SEM image of catalytic electrode; Fig.11 1 is a graph showing the variation of electrolysis voltage of oxygen evolution catalytic electrodes prepared in Example 2 and Comparative Example 1 with current density; Fig.12 is a graph showing the variation of electrolysis voltage of oxygen evolution catalytic electrodes prepared in Example 2 and Comparative Example 1 with electrolysis time; Fig.13 The Fe prepared in Example 3 3+ / Fe 2+ / Ni 2+ (OH) x @PES / TiO 2 -3 SEM image of catalytic electrode; Fig.14 is a graph showing the variation of electrolysis voltage of oxygen evolution catalytic electrodes prepared in Example 3 and Comparative Example 1 with current density; Fig.15 is a graph showing the variation of electrolysis voltage of oxygen evolution catalytic electrodes prepared in Example 3 and Comparative Example 1 with electrolysis time; Fig.16 The Fe prepared in Example 4 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / ZrO 2 -4 SEM image of catalytic electrode; Fig.17 is a graph showing the variation of electrolysis voltage of oxygen evolution catalytic electrodes prepared in Example 4 and Comparative Example 1 with current density; Fig.18 is a graph showing the variation of electrolysis voltage of oxygen evolution catalytic electrodes prepared in Example 4 and Comparative Example 1 with electrolysis time; Fig.19 The Fe prepared in Example 5 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / CeO 2-5 SEM image of catalytic electrode; Fig. 20 is a graph showing the variation of electrolysis voltage of oxygen evolution catalytic electrodes prepared in Example 5 and Comparative Example 1 with current density; Fig.21 is a graph showing the variation of electrolysis voltage of oxygen evolution catalytic electrodes prepared in Example 5 and Comparative Example 1 with electrolysis time; Fig. 22 The Fe prepared in Example 6 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / ZrO 2 -6 SEM image of catalytic electrode; Fig.23 is a graph showing the variation of electrolysis voltage of oxygen evolution catalytic electrodes prepared in Example 6 and Comparative Example 1 with current density; Fig.24 is a graph showing the variation of electrolysis voltage of oxygen evolution catalytic electrodes prepared in Example 6 and Comparative Example 1 with electrolysis time; Fig.25 This is a picture taken during the preparation of the oxygen evolution composite catalytic electrode in Example 7. DETAILED DESCRIPTION
[0020] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are merely examples of devices and methods consistent with some aspects of the present invention as detailed in the appended claims.
[0021] In a first aspect, a composite catalytic electrode for electrolyzing water and evolving oxygen is provided, comprising: A porous nickel substrate, a composite catalyst layer and a porous composite bonding layer; the composite catalyst layer is loaded on the porous nickel substrate, and the porous composite bonding layer is coated on the surface of the composite catalyst layer; the composite catalyst layer includes a nickel-iron-based hydroxide catalyst, and the porous composite bonding layer is a nanoporous polymer ceramic powder composite coating.
[0022] It can be understood that the catalyst layer of the electrode is coated with a porous composite coating. Since a porous structure is formed on the surface of the Ni mesh substrate, the composite catalyst layer can be combined with the metal substrate to form a stable structure, and the porous ceramic polymer composite coating can stably cover the surface of the composite catalyst layer, so that the composite catalytic electrode exhibits high long-term structural stability. At the same time, the prepared water electrolysis oxygen evolution composite catalytic electrode exhibits long-term operating stability when operating at a high current density, and has important industrial application value.
[0023] In another embodiment, the composite catalyst layer further comprises a catalyst promoter of molybdenum, vanadium, manganese or cobalt. The polymer in the nanoporous polymer ceramic powder composite coating is one or more of the alkali-resistant polymers polysulfone or polyethersulfone; the ceramic powder in the nanoporous polymer ceramic powder composite coating is one or more of zirconium oxide, titanium oxide, cerium oxide, and niobium oxide.
[0024] In another embodiment, the total loading of the nickel-iron-based hydroxide catalyst is 0.1-30 mg / cm 2 , the nickel-iron molar ratio is 1:50-2:1; the loading amount of the nanoporous polymer ceramic powder composite coating is 0.01-5 mg / cm 2 The mass ratio of polymer to ceramic powder is 100:1-1:20.
[0025] Preferably, the total loading of the nickel-iron-based hydroxide catalyst is 0.5-30 mg / cm 2 The molar ratio of nickel to iron is 1:4-1:1; the loading amount of the nanoporous polymer ceramic powder composite coating is 0.1-4 mg / cm 2 The mass ratio of polymer to ceramic powder is 100:1-1:20.
[0026] In another embodiment, the porous nickel substrate is a nickel mesh, a nickel felt, a nickel alloy mesh, a nickel foam or a nickel alloy foam.
[0027] In the second aspect, a method for preparing a composite catalytic electrode for oxygen evolution by electrolysis of water is provided, see Figure 1 ,include: adding a stabilizer to a nickel-iron catalyst precursor compound solution to form a catalyst solution; After coating the catalyst solution on the surface of the porous nickel substrate, the catalyst solution is reacted with an alkaline solution to form a composite catalyst layer; After coating the ceramic powder and the polymer slurry onto the surface of the composite catalyst layer, a protective layer is formed by a phase transfer method.
[0028] In another embodiment, in the method for preparing the composite catalytic electrode for oxygen evolution by electrolysis of water, the stabilizer is an amino acid, hydrochloric acid, sulfuric acid, acetic acid, nitric acid or citric acid; the iron precursor salt in the nickel-iron catalyst precursor compound solution is one or more of ferric chloride, ferric nitrate, ferric sulfate, and ferric acetate; the nickel precursor salt in the nickel-iron catalyst precursor compound solution is one or more of nickel chloride, nickel nitrate, nickel sulfate, and nickel acetate; in the nickel-iron catalyst precursor compound solution, the molar ratio of the nickel-iron precursor to the stabilizer is 1:2-50:1.
[0029] It should be noted that preferred stabilizers are acidic amino acids such as glutamic acid and aspartic acid.
[0030] After coating the catalyst solution onto the surface of the porous nickel substrate, the method further comprises: The porous nickel substrate coated with the catalyst solution is dried and then reacted in situ with an alkaline solution to form a composite catalyst layer.
[0031] In specific practice, the coating method can be any appropriate method, such as brushing, spraying, rolling, dipping or printing, preferably automatic spraying and automatic brushing. Afterwards, a drying step can be optionally included. The drying method can be room temperature drying, 30-200° C. oven drying, preferably 50-100° C. drying.
[0032] The coating, ion adsorption, optional drying and in-situ reaction process can be repeated, and the above process can be performed 1-20 times, preferably 1-5 times. It is understood that the catalyst reaches the desired loading amount by repeating the above process once or multiple times.
[0033] After the composite catalyst layer is formed, it needs to be coated with a porous composite protective layer. The ceramic powder in the configured ceramic powder and polymer slurry is an oxide or composite oxide of a metal chemical element, such as titanium, cerium, zirconium, yttrium, niobium, tantalum, and lanthanum; the polymer in the ceramic powder and polymer slurry is an alkali-resistant polymer, polysulfone, and polyethersulfone; the slurry solvent in the ceramic powder and polymer slurry is a solution that can dissolve an alkali-resistant polymer, such as N-methyl-2-pyrrolidone, N-methylpyrrolidone, etc.
[0034] The slurry is mixed uniformly by mechanical stirring, ball milling and the like, and the mixing time is 1-200h, preferably 24-60h. The slurry is then applied to the surface of the catalyst layer. The coating method can be brushing, spraying, rolling, dipping or printing, preferably automatic spraying and automatic brushing methods. After coating, a phase transfer or drying step can be optionally performed to form a porous composite coating on the surface of the catalyst layer. The above-mentioned coating, optionally phase transfer or drying process can be repeated, and the above-mentioned process can be performed 1-10 times, preferably 1-3 times. The porous composite coating reaches the expected loading amount by repeating the above-mentioned coating, optionally phase transfer and drying process once or multiple times.
[0035] In addition to the above steps, other auxiliary steps may also be included, such as cleaning, drying, and roughening of the nickel substrate. By roughening the nickel substrate, the adhesion of the catalyst layer to the substrate can be improved. The treatment process may be to select a substrate such as a nickel mesh, a nickel alloy mesh, a foamed nickel or a foamed nickel alloy, and then pretreat the substrate. The pretreatment process includes: sandblasting the nickel substrate with a sandblaster, preferably an automatic sandblaster; ultrasonic treatment to remove the corundum particles on the surface of the substrate; preparing an acidic solution such as hydrochloric acid, sulfuric acid, nitric acid or acetic acid, etching the sandblasted nickel substrate under ultrasonic conditions, removing the highly active nickel particles on the surface and forming a porous structure; washing with water, drying to obtain a rough nickel substrate, and then using a roller press to level the sandblasted nickel substrate. When the nickel substrate is a nickel mesh or a nickel alloy mesh, a plain or twill mesh with a mesh size of 10-500 and a wire diameter of 0.03-4 mm can be used, preferably a plain nickel mesh with a mesh size of 20-80 and a wire diameter of 0.1-0.5 mm. The sandblasting power of the sandblasting machine is: 5-50kW, preferably 10-20kW; sandblasting time: 5min-2h, preferably 10-40min. The corundum models for sandblasting are 24, 46, 60, 80, preferably 46 and 60. The sandblasting treatment includes single-sided sandblasting or double-sided sandblasting of the nickel substrate, preferably double-sided sandblasting. The concentration of the acid etching solution is 0.005mol / L-2.0mol / L, preferably 0.02mol / L-0.2mol / L. The etching time is 10min-24h, preferably 1h-4h. The ultrasonic power of etching is 50W-2000W, preferably 400W-600W. The ultrasonic frequency is 10KHz-98KHz, preferably 20KHz-40KHz. The ultrasonic etching temperature is room temperature-100℃, preferably 30℃-60℃.
[0036] According to a third aspect of the present invention, a water electrolysis hydrogen evolution device is provided, wherein the electrode of the water electrolysis hydrogen evolution device is any one of the above-mentioned water electrolysis oxygen evolution composite catalytic electrodes.
[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the following provides Examples 1 to 8, as well as Comparative Example 1 and Comparative Example 2, and the technical scheme of the present invention is described in detail. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work belong to the scope of protection of the present invention.
[0038] Table 1 summarizes the oxygen evolution composite catalytic electrodes of Examples 1-8, Comparative Example 1 and Comparative Example 2 at current densities of 200-2000 mA / cm 2 The power saving rate under the condition of 1500mA / cm 2The voltage rise rate after running for 240h at the current density is as follows: compared with the porous Ni mesh electrode in Comparative Example 1, the energy consumption of hydrogen production by electrolysis of water in the composite catalytic electrode of Examples 1-8 is reduced by 10.1-16.8%; and at 1500mA / cm 2 After running for 240 hours at a high current density, the electrolysis voltages of Comparative Examples 1 and 2 increased by 30.4% and 25.5%, respectively, while the electrolysis voltages of Examples 1-8 only increased by 0.4-1.3%, indicating that compared with Comparative Examples 1 and 2, the catalytic electrodes of Examples 1-8 have higher water electrolysis operation stability.
[0039] Table 1 Comparison of power saving rate and voltage increase rate of oxygen evolution composite electrode
[0040] 1. Power saving rate = (electrolysis voltage of comparative example 1 - electrolysis voltage of embodiment) / electrolysis voltage of comparative example 1 × 100%.
[0041] 2. Voltage rise rate = (catalytic electrode at 1500mA / cm 2 Electrolysis voltage after running for 240 hours at current density (electrolysis voltage - starting electrolysis voltage) / starting electrolysis voltage × 100%. The lower the voltage increase rate, the higher the stability of the oxygen evolution electrode.
[0042] Example 1 A 46-mesh plain nickel mesh was selected as the substrate, and the nickel mesh was sandblasted for 40 minutes using an automatic sandblasting machine, No. 60 corundum, and 15kW power. The corundum particles on the surface were removed by ultrasonic treatment for 1 hour, and then a 0.2 mol / L hydrochloric acid solution was prepared and the sandblasted nickel mesh was etched for 1 hour under ultrasonic conditions (ultrasonic power of 900 W, ultrasonic frequency of 28 KHz, and ultrasonic etching temperature of 30°C), washed with water, and dried to obtain a nickel mesh substrate with a porous surface structure.
[0043] Prepare 0.3 mol / L ferric chloride and 0.2 mol / L nickel chloride aqueous solution, add amino acid stabilizer at the same time, the molar ratio of ferric chloride to amino acid is 5:1, mix well, and obtain iron-nickel precursor solution. Apply the iron-nickel precursor to the surface of the porous nickel mesh by automatic spraying, and after drying in an oven at 80°C, Fe 3+ / Fe 2+ / Ni 2+ Compound. Prepare 2.0 mol / L sodium hydroxide and 1.5 mol / L ammonium chloride aqueous solution, and apply the sodium hydroxide and ammonium chloride aqueous solution to the Fe by automatic spraying. 3+ / Fe 2+ / Ni 2+ On the surface of the compound, after in-situ reaction in an oven at 60°C, Fe 3+ / Fe 2+ / Ni 2+ The hydroxide catalyst layer, after ultrasonic and water washing treatment, has a catalyst layer loading of 1.5-2.0 mg / cm 2 .
[0044] Prepare a uniform slurry of polyethersulfone (PES): zirconium oxide (mass ratio) = 2:1, polyethersulfone and zirconium oxide: NMP (mass ratio) = 5:100, apply it to the surface of the catalyst layer, and then immerse it in deionized water for 48 hours to form a porous composite coating on the surface of the catalyst layer by phase transfer. The loading amount of the composite coating is about 0.15mg / cm 2 , Fe coated with porous composite coating was prepared 3 + / Fe 2+ / Ni 2+ The hydroxide composite catalytic electrode, named Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PES / ZrO 2 -1, the schematic diagram of the preparation process is as follows Figure 1 shown. Figure 2 The SEM image shows that the surface of the composite catalytic electrode is covered with a layer of porous composite coating.
[0045] Comparative Example 1 This comparative example is compared with Example 1, the difference is that no Fe is grown in situ on the surface of the porous Ni mesh. 3+ / Fe 2+ / Ni 2+ Hydroxide composite catalytic layer. A 46-mesh plain nickel mesh was selected as the substrate, and an automatic sandblasting machine, No. 60 corundum, and 15kW power were used to sandblast the nickel mesh for 40 minutes. The corundum particles on the surface were removed by ultrasonic treatment for 1 hour, and then a 0.2 mol / L hydrochloric acid solution was prepared. The sandblasted nickel mesh was etched for 1 hour under ultrasonic conditions (ultrasonic power of 900 W, ultrasonic frequency of 28 KHz, and ultrasonic etching temperature of 30°C). After washing and drying, a nickel mesh catalytic electrode with a porous structure on the surface was obtained, which was named porous Ni mesh. The SEM picture is shown as follows: Figure 3 shown.
[0046] Comparative Example 2 This comparative example is compared with Example 1, except that no Fe 3+ / Fe 2+ / Ni 2+The surface of the hydroxide composite electrode is coated with a porous composite coating. A 46-mesh plain nickel mesh is selected as the substrate, and the nickel mesh is sandblasted for 40 minutes using an automatic sandblasting machine, No. 60 corundum, and 15kW power. The corundum particles on the surface are removed by ultrasonic treatment for 1 hour, and then a 0.2 mol / L hydrochloric acid solution is prepared, and the sandblasted nickel mesh is etched for 1 hour under ultrasonic conditions (ultrasonic power of 900 W, ultrasonic frequency of 28 KHz, ultrasonic etching temperature of 30 ° C), washed with water, and dried to obtain a nickel mesh substrate with a porous surface structure.
[0047] Prepare 0.3 mol / L ferric chloride and 0.2 mol / L nickel chloride aqueous solution, add amino acid stabilizer, the molar ratio of ferric chloride to amino acid is 5:1, mix well, and obtain iron-nickel precursor solution. Apply the iron-nickel precursor to the surface of the nickel mesh by automatic spraying, and after drying in an oven at 80°C, Fe 3+ / Fe 2+ / Ni 2+ Compound. Prepare 2.0 mol / L sodium hydroxide and 1.5 mol / L ammonium chloride aqueous solution, and apply the sodium hydroxide and ammonium chloride aqueous solution to the Fe by automatic spraying. 3+ / Fe 2+ / Ni 2+ On the surface of the compound, after in-situ reaction in an oven at 60°C, Fe 3+ / Fe 2+ / Ni 2+ The hydroxide catalyst layer, named Fe 3+ / Fe 2+ / Ni 2+ (OH) x After ultrasonic and water washing treatment, the catalyst layer loading is 1.5-2.0 mg / cm 2 , the SEM image of the surface structure is as follows Figure 4 shown.
[0048] The beneficial effects of the present invention are as follows: (1) In the absence of ultrasound during the acid etching process, a porous structure cannot be formed on the surface of the nickel mesh, such as Figure 5 As shown in the SEM image; (2) in Fe 3+ / Ni 2+ Adding amino acid stabilizer to the ion adsorption solution can make the coating solution maintain long-term stability. Without adding amino acid stabilizer, Fe 3+ / Ni 2+ The aqueous solution will precipitate after about 48-96 hours, and the precursor solution cannot be stable for a long time; (3) In the in situ reaction process, only NaOH or KOH is added. 3+ / Fe 2+ / Ni 2+It will react quickly to form hydroxide. The catalyst particles are large. When NH 4 Cl or NH 4 F buffer conditions, the Fe 3+ / Fe 2+ / Ni 2+ The nano-sized hydroxide catalyst particles improve the catalytic activity; (4) 3+ / Fe 2+ / Ni 2+ The porous composite coating on the surface of the hydroxide catalyst layer can significantly improve the operating stability of the catalytic electrode at high current density. After coating with the porous composite coating, especially when the current density is greater than 1A / m 2 Under these conditions, the operating stability is significantly improved.
[0049] Performance Test: Test method: A two-chamber electrolytic cell was used, and the anode was the Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PES / ZrO 2 -1 oxygen evolution electrode, the porous Ni mesh oxygen evolution electrode prepared in comparative example 1, the Fe 3+ / Fe 2+ / Ni 2+ (OH) x Oxygen evolution electrode, cathode is titanium oxide coated platinum nickel composite catalytic electrode, diaphragm is composite diaphragm, the electrode working area of anode and cathode is 10cm 2 Each composite catalytic electrode was loaded with 3 pieces, and a 6-chamber electrolyzer was used for comparative testing. During the test, a peristaltic pump was used to introduce electrolyte into the electrolyzer. A 30wt% KOH aqueous solution was introduced into the anode and cathode at a flow rate of 150rpm / min, respectively, and the test temperature was 80℃. (1) The test current density was 200mA / cm 2 , 500mA / cm 2 , 1000mA / cm 2 , 1500mA / cm 2 , 2000mA / cm 2 (2) Tested at 1500mA / cm 2 The stability for 240h under high current density was observed using a scanning electron microscope to observe the electrode surface morphology after the test and compare the electrode structure stability.
[0050] Test results: When the anode is Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PES / ZrO 2-1 (Example 1), the current density is 200mA / cm 2 -2000mA / cm 2 , the voltage for water splitting is between 1.56V and 2.43V, while when the anode is a porous Ni mesh (Comparative Example 1), the voltage for water splitting is between 1.79V and 2.85V, and Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PES / ZrO 2 -1 Compared with porous Ni mesh, the energy consumption of water decomposition is reduced by 12.8-14.7% (see Figure 6 ), and at 1500mA / cm 2 After running at a high current density for 240 h, the voltage of water splitting can still be maintained at 2.24 V, while the Fe 3+ / Fe 2+ / Ni 2+ (OH) x After the catalytic electrode was operated for 240 hours, the voltage increased to 2.76V, and after the porous Ni mesh electrode of Comparative Example 1 was operated for 240 hours, the voltage increased to 3.35V (see Figure 7 ). By comparison, it can be seen that the PES / ZrO 2 Coated Fe 3+ / Fe 2+ / Ni 2+ (OH) x The catalytic electrode showed higher catalytic activity and long-term stability in water electrolysis than the porous Ni mesh electrode in Comparative Example 1, which prolonged the service life of the composite catalytic electrode and reduced energy consumption. 3+ / Fe 2+ / Ni 2+ (OH) x Most of the catalytic layer on the surface of the catalytic electrode has fallen off (see the surface SEM image). Figure 8 ), while the PES / ZrO of Example 1 2 Coated Fe 3+ / Fe 2+ / Ni 2+ (OH) x The catalytic electrode structure is stable and maintains the original catalytic layer structure (see surface SEM image Fig. 9 ), indicating that the composite oxygen evolution catalytic electrode has high structural stability when operating at high current density.
[0051] Example 2 A 46-mesh plain nickel mesh was selected as the substrate, and the nickel mesh was sandblasted for 40 minutes using an automatic sandblasting machine, No. 60 corundum, and 15kW power. The corundum particles on the surface were removed by ultrasonic treatment for 1 hour, and then a 0.2 mol / L hydrochloric acid solution was prepared and the sandblasted nickel mesh was etched for 1 hour under ultrasonic conditions (ultrasonic power of 900 W, ultrasonic frequency of 28 KHz, and ultrasonic etching temperature of 30°C), washed with water, and dried to obtain a nickel mesh substrate with a porous surface structure.
[0052] Prepare 0.3 mol / L ferric chloride and 0.1 mol / L nickel chloride aqueous solution, add amino acid stabilizer at the same time, the molar ratio of ferric chloride to amino acid is 4:1, mix well, and obtain iron-nickel precursor solution. Apply the iron-nickel precursor to the surface of the nickel mesh by brushing, and after drying in an oven at 80°C, Fe 3+ / Fe 2+ / Ni 2+ Compound. Prepare 3.0 mol / L sodium hydroxide and 1.5 mol / L ammonium chloride aqueous solution, and apply the sodium hydroxide and ammonium chloride aqueous solution to the Fe by brushing. 3+ / Fe 2+ / Ni 2+ On the surface of the compound, after in-situ reaction in an oven at 60°C, Fe 3+ / Fe 2+ / Ni 2+ The hydroxide catalyst layer, after ultrasonic and water washing treatment, was repeatedly coated with nickel-iron precursor solution, ion adsorption, alkaline solution, in-situ reaction, ultrasonic and water washing treatment once, and the catalyst layer loading was 2.6-3.3 mg / cm 2 .
[0053] Prepare a uniform slurry of polyethersulfone (PES): zirconium oxide (mass ratio) = 3:1, polyethersulfone and zirconium oxide: NMP (mass ratio) = 6:100, brush it on the surface of the catalyst layer, and then immerse it in deionized water for 48 hours to form a porous composite coating on the surface of the catalyst layer by phase transfer. Repeat once. The composite coating loading is about 0.21 mg / cm 2 , Fe coated with porous composite coating was prepared 3+ / Fe 2+ / Ni 2+ The hydroxide composite catalytic electrode, named Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PES / ZrO 2 -2. Fig.10 The SEM image shows that the surface of the composite catalytic electrode is covered with a layer of porous composite coating.
[0054] Performance Test: Test method: A two-chamber electrolytic cell was used, and the anode was the Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PES / ZrO 2 -2. The porous Ni mesh catalytic electrode prepared in Comparative Example 1, the cathode is a titanium oxide-coated platinum-nickel composite catalytic electrode, the diaphragm is a composite diaphragm, and the electrode working area of the anode and cathode is 10 cm 2 Each composite catalytic electrode was loaded with 3 pieces, and a 6-chamber electrolyzer was used for comparative testing. During the test, a peristaltic pump was used to introduce electrolyte into the electrolyzer. A 30wt% KOH aqueous solution was introduced into the anode and cathode at a flow rate of 150rpm / min, respectively, and the test temperature was 80℃. (1) The test current density was 200mA / cm 2 , 500mA / cm 2 , 1000mA / cm 2 , 1500mA / cm 2 , 2000mA / cm 2 (2) Tested at 1500mA / cm 2 240h stability at high current density.
[0055] Test results: When the anode is Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PES / ZrO 2 -2 (Example 2), the current density is 200mA / cm 2 -2000mA / cm 2 , the voltage for water splitting is between 1.61V and 2.46V, while when the anode is a porous Ni mesh (Comparative Example 1), the voltage for water splitting is between 1.79V and 2.85V, and Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PES / ZrO 2 -2 reduces energy consumption by 10.1-13.7% compared to porous Ni mesh electrodes (see Fig.11 ), and at 1500mA / cm 2 After running at a high current density of 240 h, the voltage of the complete water splitting can still be maintained at 2.32 V, while the voltage of the porous Ni mesh electrode of Comparative Example 1 increased to 3.35 V after running for 240 h (see Fig.12 ). By comparison, it can be seen that the PES / ZrO 2 Coated Fe 3+ / Fe 2+ / Ni2+ (OH) x The catalytic electrode exhibits higher catalytic activity and long-term stability in water electrolysis than the porous Ni mesh electrode, which increases the service life of the composite catalytic electrode and reduces energy consumption.
[0056] Example 3 A 46-mesh plain nickel mesh was selected as the substrate, and the nickel mesh was sandblasted for 40 minutes using an automatic sandblasting machine, No. 60 corundum, and 15kW power. The corundum particles on the surface were removed by ultrasonic treatment for 1 hour, and then a 0.2 mol / L hydrochloric acid solution was prepared and the sandblasted nickel mesh was etched for 1 hour under ultrasonic conditions (ultrasonic power of 900 W, ultrasonic frequency of 28 KHz, and ultrasonic etching temperature of 30°C), washed with water, and dried to obtain a nickel mesh substrate with a porous surface structure.
[0057] Prepare a 0.3 mol / L ferric chloride aqueous solution, add an amino acid stabilizer, and mix well to obtain an iron precursor solution. Apply the iron precursor to the surface of the nickel mesh by automatic spraying, and after drying in an oven at 80°C, Fe 3+ / Fe 2+ / Ni 2+ Compound. Prepare 3.0 mol / L potassium hydroxide and 1.5 mol / L ammonium chloride aqueous solution, and apply the potassium hydroxide and ammonium chloride aqueous solution to the Fe by automatic spraying. 3+ / Fe 2 + / Ni 2+ On the surface of the compound, after in-situ reaction in an oven at 60°C, Fe 3+ / Fe 2+ / Ni 2+ The hydroxide catalyst layer, after ultrasonic and water washing treatment, has a catalyst layer loading of 1.2-1.6 mg / cm 2 .
[0058] Prepare a uniform slurry of polyethersulfone (PES): titanium oxide (mass ratio) = 4:1, polyethersulfone and titanium oxide: NMP (mass ratio) = 5:100, apply it to the surface of the catalyst layer, and then immerse it in deionized water for 48 hours to form a porous composite coating on the surface of the catalyst layer by phase transfer. The loading amount of the composite coating is about 0.13mg / cm 2 , Fe coated with porous composite coating was prepared 3 + / Fe 2+ / Ni 2+ The hydroxide composite catalytic electrode, named Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PES / TiO2 -3. Fig.13 The SEM image shows that the surface of the composite catalytic electrode is covered with a layer of porous composite coating.
[0059] Performance Test: Test method: A two-chamber electrolytic cell was used, and the anode was the Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PES / TiO 2 -3. The porous Ni mesh catalytic electrode prepared in Comparative Example 1, the cathode is a titanium oxide-coated platinum-nickel composite catalytic electrode, the diaphragm is a composite diaphragm, and the electrode working area of the anode and cathode is 10 cm 2 Each composite catalytic electrode was loaded with 3 pieces, and a 6-chamber electrolyzer was used for comparative testing. During the test, a peristaltic pump was used to introduce electrolyte into the electrolyzer. A 30wt% KOH aqueous solution was introduced into the anode and cathode at a flow rate of 150rpm / min, respectively, and the test temperature was 80℃. (1) The test current density was 200mA / cm 2 , 500mA / cm 2 , 1000mA / cm 2 , 1500mA / cm 2 , 2000mA / cm 2 (2) Tested at 1500mA / cm 2 240h stability at high current density.
[0060] Test results: When the anode is Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PES / TiO 2 -3 (Example 3), the current density is 200mA / cm 2 -2000mA / cm 2 , the voltage for water splitting is between 1.52V and 2.39V, while when the anode is a porous Ni mesh (Comparative Example 1), the voltage for water splitting is between 1.79V and 2.85V, and Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PES / TiO 2 -3 reduces energy consumption by 15.1-16.1% compared to porous Ni mesh electrodes (see Fig.14 ), and at 1500mA / cm 2After running at a high current density of 240 h, the voltage of the complete water splitting can still be maintained at 2.26 V, while the voltage of the porous Ni mesh electrode of Comparative Example 1 increased to 3.35 V after running for 240 h (see Fig.15 ). By comparison, it can be seen that the PES / TiO 2 Coated Fe 3+ / Fe 2+ / Ni 2+ (OH) x The catalytic electrode exhibits higher catalytic activity and long-term stability in water electrolysis than the porous Ni mesh electrode, which increases the service life of the composite catalytic electrode and reduces energy consumption.
[0061] Example 4 A 46-mesh plain nickel mesh was selected as the substrate, and the nickel mesh was sandblasted for 40 minutes using an automatic sandblasting machine, No. 60 corundum, and 15kW power. The corundum particles on the surface were removed by ultrasonic treatment for 1 hour, and then a 0.2 mol / L hydrochloric acid solution was prepared and the sandblasted nickel mesh was etched for 1 hour under ultrasonic conditions (ultrasonic power of 900 W, ultrasonic frequency of 28 KHz, and ultrasonic etching temperature of 30°C), washed with water, and dried to obtain a nickel mesh substrate with a porous surface structure.
[0062] Prepare 0.5 mol / L ferric chloride and 0.15 mol / L nickel chloride aqueous solution, add amino acid stabilizer, the molar ratio of ferric chloride to amino acid is 4:1, mix well, and obtain iron-nickel precursor solution. Apply the iron-nickel precursor to the surface of the nickel mesh by automatic spraying, and after drying in an oven at 80°C, Fe 3+ / Fe 2+ / Ni 2+ Compound. Prepare 3.0 mol / L potassium hydroxide and 1.5 mol / L ammonium fluoride aqueous solution, and apply the potassium hydroxide and ammonium fluoride aqueous solution to the Fe by automatic spraying. 3+ / Fe 2+ / Ni 2+ On the surface of the compound, after in-situ reaction in an oven at 60°C, Fe 3+ / Fe 2+ / Ni 2+ The hydroxide catalyst layer, after ultrasonic and water washing treatment, has a catalyst layer loading of 1.2-1.6 mg / cm 2 .
[0063] Prepare a uniform slurry of polysulfone (PSF): zirconium oxide (mass ratio) = 6:1, polysulfone and zirconium oxide: NMP (mass ratio) = 5:100, apply it to the surface of the catalyst layer, and then immerse it in deionized water for 48 hours to form a porous composite coating on the surface of the catalyst layer by phase transfer. The composite coating loading is about 0.12mg / cm 2, Fe coated with porous composite coating was prepared 3+ / Fe 2+ / Ni 2+ The hydroxide composite catalytic electrode, named Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / ZrO 2 -4. Fig.16 The SEM image shows that the surface of the composite catalytic electrode is covered with a layer of porous composite coating.
[0064] Performance Test: Test method: A two-chamber electrolytic cell was used, and the anode was the Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / ZrO 2 -4. The porous Ni mesh catalytic electrode prepared in Comparative Example 1, the cathode is a titanium oxide-coated platinum-nickel composite catalytic electrode, the diaphragm is a composite diaphragm, and the electrode working area of the anode and cathode is 10 cm 2 Each composite catalytic electrode was loaded with 3 pieces, and a 6-chamber electrolyzer was used for comparative testing. During the test, a peristaltic pump was used to introduce electrolyte into the electrolyzer. A 30wt% KOH aqueous solution was introduced into the anode and cathode at a flow rate of 150rpm / min, respectively, and the test temperature was 80℃. (1) The test current density was 200mA / cm 2 , 500mA / cm 2 , 1000mA / cm 2 , 1500mA / cm 2 , 2000mA / cm 2 (2) Tested at 1500mA / cm 2 240h stability at high current density.
[0065] Test results: When the anode is Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / ZrO 2 -4 (Example 4), the current density is 200mA / cm 2 -2000mA / cm 2 , the voltage for water splitting is between 1.56V and 2.44V, while when the anode is a porous Ni mesh (Comparative Example 1), the voltage for water splitting is between 1.79V and 2.85V, and Fe 3+ / Fe 2+ / Ni 2+ (OH) x@PSF / ZrO 2 -4 reduces energy consumption by 12.8-14.4% compared to porous Ni mesh electrodes (see Fig.17 ), and at 1500mA / cm 2 After running at a high current density of 240 h, the voltage of the complete water splitting can still be maintained at 2.29 V, while the voltage of the porous Ni mesh electrode of Comparative Example 1 increased to 3.35 V after running for 240 h (see Fig.18 ). By comparison, it can be seen that the PSF / ZrO 2 Coated Fe 3+ / Fe 2+ / Ni 2+ (OH) x The catalytic electrode exhibits higher catalytic activity and long-term stability in water electrolysis than the porous Ni mesh electrode, which increases the service life of the composite catalytic electrode and reduces energy consumption.
[0066] Example 5 A 46-mesh plain nickel mesh was selected as the substrate, and the nickel mesh was sandblasted for 40 minutes using an automatic sandblasting machine, No. 60 corundum, and 15kW power. The corundum particles on the surface were removed by ultrasonic treatment for 1 hour, and then a 0.2 mol / L hydrochloric acid solution was prepared and the sandblasted nickel mesh was etched for 1 hour under ultrasonic conditions (ultrasonic power of 900 W, ultrasonic frequency of 28 KHz, and ultrasonic etching temperature of 30°C), washed with water, and dried to obtain a nickel mesh substrate with a porous surface structure.
[0067] Prepare 0.5 mol / L ferric chloride and 0.2 mol / L nickel nitrate aqueous solution, add amino acid stabilizer at the same time, the molar ratio of ferric chloride to amino acid is 4:1, mix well, and obtain iron-nickel precursor solution. Apply the iron-nickel precursor to the surface of the nickel mesh by automatic spraying, and after drying in an oven at 80°C, Fe 3+ / Fe 2+ / Ni 2+ Compound. Prepare 3.0 mol / L sodium hydroxide and 1.5 mol / L ammonium chloride aqueous solution, and apply the sodium hydroxide and ammonium chloride aqueous solution to the Fe by automatic spraying. 3+ / Fe 2+ / Ni 2+ On the surface of the compound, after in-situ reaction in an oven at 60°C, Fe 3+ / Fe 2+ / Ni 2+ The hydroxide catalyst layer, after ultrasonic and water washing treatment, has a catalyst layer loading of 1.5-1.8 mg / cm 2 .
[0068] Prepare a uniform slurry of polysulfone (PSF): cerium oxide (mass ratio) = 8:1, polysulfone and cerium oxide: NMP (mass ratio) = 10:100, brush it on the surface of the catalyst layer, and then immerse it in deionized water for 48 hours to form a porous composite coating on the surface of the catalyst layer by phase transfer. The composite coating loading is about 0.21mg / cm 2 , Fe coated with porous composite coating was prepared 3+ / Fe 2 + / Ni 2+ The hydroxide composite catalytic electrode, named Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / CeO 2 -5. Fig.19 The SEM image shows that the surface of the composite catalytic electrode is covered with a layer of porous composite coating.
[0069] Performance Test: Test method: A two-chamber electrolytic cell was used, and the anode was the Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / CeO 2 -5. The porous Ni mesh catalytic electrode prepared in Comparative Example 1, the cathode is a titanium oxide-coated platinum-nickel composite catalytic electrode, the diaphragm is a composite diaphragm, and the electrode working area of the anode and cathode is 10 cm 2 Each composite catalytic electrode was loaded with 3 pieces, and a 6-chamber electrolyzer was used for comparative testing. During the test, a peristaltic pump was used to introduce electrolyte into the electrolyzer. A 30wt% KOH aqueous solution was introduced into the anode and cathode at a flow rate of 150rpm / min, respectively, and the test temperature was 80℃. (1) The test current density was 200mA / cm 2 , 500mA / cm 2 , 1000mA / cm 2 , 1500mA / cm 2 , 2000mA / cm 2 (2) Tested at 1500mA / cm 2 240h stability at high current density.
[0070] Test results: When the anode is Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / CeO 2 -5 (Example 5), the current density is 200mA / cm 2-2000mA / cm 2 , the voltage for water splitting is between 1.50V and 2.39V, while when the anode is a porous Ni mesh (Comparative Example 1), the voltage for water splitting is between 1.79V and 2.85V, and Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / CeO 2 -5 reduces energy consumption by 16.1-16.2% compared with porous Ni mesh electrode (see Fig. 20 ), and at 1500mA / cm 2 After running at a high current density of 240 h, the voltage of the complete water splitting can still be maintained at 2.23 V, while the voltage of the porous Ni mesh electrode of Comparative Example 1 increased to 3.35 V after running for 240 h (see Fig.21 ). By comparison, it can be seen that the PSF / CeO 2 Coated Fe 3+ / Fe 2+ / Ni 2+ (OH) x The catalytic electrode exhibits higher catalytic activity and long-term stability in water electrolysis than the porous Ni mesh electrode, which increases the service life of the composite catalytic electrode and reduces energy consumption.
[0071] Example 6 A 46-mesh twill nickel mesh was selected as the substrate, and the nickel mesh was sandblasted for 40 minutes using an automatic sandblasting machine, No. 60 corundum, and 15kW power. The corundum particles on the surface were removed by ultrasonic treatment for 1 hour, and then a 0.2 mol / L hydrochloric acid solution was prepared and the sandblasted nickel mesh was etched for 1 hour under ultrasonic conditions (ultrasonic power of 900 W, ultrasonic frequency of 28 KHz, and ultrasonic etching temperature of 30°C), washed with water, and dried to obtain a nickel mesh substrate with a porous surface structure.
[0072] Prepare 0.3 mol / L ferric nitrate and 0.3 mol / L nickel chloride aqueous solution, add amino acid stabilizer at the same time, the molar ratio of ferric nitrate to amino acid is 4:1, mix well, and obtain iron-nickel precursor solution. Apply the iron-nickel precursor to the surface of the nickel mesh by automatic spraying, and after drying in an oven at 60°C, Fe 3+ / Fe 2+ / Ni 2+ Compound. Prepare 3.0 mol / L sodium hydroxide and 1.5 mol / L ammonium chloride aqueous solution, and apply the sodium hydroxide and ammonium chloride aqueous solution to the Fe by automatic spraying. 3+ / Fe 2+ / Ni 2+ On the surface of the compound, after in-situ reaction in an oven at 60°C, Fe 3+ / Fe 2+ / Ni2+ The hydroxide catalyst layer, after ultrasonic and water washing treatment, has a catalyst layer loading of 1.7-2.0 mg / cm 2 .
[0073] Prepare a uniform slurry of polysulfone (PSU): zirconium oxide (mass ratio) = 8:1, polysulfone and zirconium oxide: NMP (mass ratio) = 6:100, apply it to the surface of the catalyst layer, and then immerse it in deionized water for 48 hours to form a porous composite coating on the surface of the catalyst layer by phase transfer. The loading amount of the composite coating is about 0.15mg / cm 2 , Fe coated with porous composite coating was prepared 3+ / Fe 2+ / Ni 2+ The hydroxide composite catalytic electrode, named Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSU / ZrO 2 -6. Fig. 22 The SEM image shows that the surface of the composite catalytic electrode is covered with a layer of porous composite coating.
[0074] Performance Test: Test method: A two-chamber electrolytic cell was used, and the anode was the Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSU / ZrO 2 -6. The porous Ni mesh catalytic electrode prepared in Comparative Example 1, the cathode is a titanium oxide-coated platinum-nickel composite catalytic electrode, the diaphragm is a composite diaphragm, and the electrode working area of the anode and cathode is 10 cm 2 Each composite catalytic electrode was loaded with 3 pieces, and a 6-chamber electrolyzer was used for comparative testing. During the test, a peristaltic pump was used to introduce electrolyte into the electrolyzer. A 30wt% KOH aqueous solution was introduced into the anode and cathode at a flow rate of 150rpm / min, respectively, and the test temperature was 80℃. (1) The test current density was 200mA / cm 2 , 500mA / cm 2 , 1000mA / cm 2 , 1500mA / cm 2 , 2000mA / cm 2 (2) Tested at 1500mA / cm 2 240h stability at high current density.
[0075] Test results: When the anode is Fe 3+ / Fe 2+ / Ni 2+(OH) x @PSU / ZrO 2 -6 (Example 6), the current density is 200mA / cm 2 -2000mA / cm 2 , the voltage for water splitting is between 1.60V and 2.51V, while when the anode is a porous Ni mesh (Comparative Example 1), the voltage for water splitting is between 1.79V and 2.85V, and Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSU / ZrO 2 -6 reduces energy consumption by 10.6-11.9% compared to porous Ni mesh electrodes (see Fig.23 ), and at 1500mA / cm 2 After running at a high current density of 240 h, the voltage of the complete water splitting can still be maintained at 2.38 V, while the voltage of the porous Ni mesh electrode of Comparative Example 1 increased to 3.35 V after running for 240 h (see Fig.24 ). By comparison, it can be seen that the PSU / ZrO 2 Coated Fe 3+ / Fe 2+ / Ni 2+ (OH) x The catalytic electrode exhibits higher catalytic activity and long-term stability in water electrolysis than the porous Ni mesh electrode, which increases the service life of the composite catalytic electrode and reduces energy consumption.
[0076] Example 7 A 46-mesh plain nickel mesh was selected as the substrate, and the nickel mesh was sandblasted for 40 minutes using an automatic sandblasting machine, No. 60 corundum, and 15kW power. The corundum particles on the surface were removed by ultrasonic treatment for 1 hour, and then a 0.2 mol / L hydrochloric acid solution was prepared and the sandblasted nickel mesh was etched for 1 hour under ultrasonic conditions (ultrasonic power of 900 W, ultrasonic frequency of 28 KHz, and ultrasonic etching temperature of 30°C), washed with water, and dried to obtain a nickel mesh substrate with a porous surface structure.
[0077] Prepare 0.3 mol / L ferric chloride and 0.3 mol / L nickel sulfate aqueous solution, add amino acid stabilizer at the same time, the molar ratio of ferric chloride to amino acid is 4:1, mix well, and obtain iron-nickel precursor solution. Apply the iron-nickel precursor to the surface of the nickel mesh by automatic spraying, and after drying in an oven at 60°C, Fe 3+ / Fe 2+ / Ni 2+ Compound. Prepare 3.0 mol / L sodium hydroxide and 1.5 mol / L ammonium chloride aqueous solution, and apply the sodium hydroxide and ammonium chloride aqueous solution to the Fe by automatic spraying. 3+ / Fe 2+ / Ni 2+ On the surface of the compound, after in-situ reaction in an oven at 60°C, Fe 3+ / Fe 2+ / Ni 2+ The hydroxide catalyst layer was treated with ultrasound and water for 3 times, and the catalyst layer loading was 4.6-5.1 mg / cm 2 .
[0078] Prepare a uniform slurry of polysulfone (PSU): zirconium oxide (mass ratio) = 80:1, polysulfone and zirconium oxide: NMP (mass ratio) = 6:100, brush it on the surface of the catalyst layer, and then immerse it in deionized water for 48 hours to form a porous composite coating on the surface of the catalyst layer by phase transfer. Repeat twice. The composite coating loading is about 0.21mg / cm 2 , Fe coated with porous composite coating was prepared 3+ / Fe 2+ / Ni 2+ The hydroxide composite catalytic electrode, named Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSU / ZrO 2 -7, preparation of composite catalytic electrode with a diameter of 30cm Fig.25 shown.
[0079] Performance Test: Test method: A two-chamber electrolytic cell was used, and the anode was the Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSU / ZrO 2 -7. The porous Ni mesh catalytic electrode prepared in Comparative Example 1, the cathode is a titanium oxide-coated platinum-nickel composite catalytic electrode, the diaphragm is a composite diaphragm, and the electrode working area of the anode and cathode is 10 cm 2 Each composite catalytic electrode was loaded with 3 pieces, and a 6-chamber electrolyzer was used for comparative testing. During the test, a peristaltic pump was used to introduce electrolyte into the electrolyzer. A 30wt% KOH aqueous solution was introduced into the anode and cathode at a flow rate of 150rpm / min, respectively, and the test temperature was 80℃. (1) The test current density was 200mA / cm 2 , 500mA / cm 2 , 1000mA / cm 2 , 1500mA / cm 2 , 2000mA / cm 2 (2) Tested at 1500mA / cm 2 240h stability at high current density.
[0080] Test results: When the anode is Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSU / ZrO 2 -7 (Example 7), the current density is 200mA / cm 2 -2000mA / cm 2 , the voltage for water splitting is between 1.51V and 2.37V, while when the anode is a porous Ni mesh (Comparative Example 1), the voltage for water splitting is between 1.79V and 2.85V, and Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSU / ZrO 2 -7 has 15.6-16.8% lower energy consumption than porous Ni mesh electrode, and at 1500mA / cm 2 After running for 240 hours at a high current density, the voltage of the complete water splitting can still be maintained at 2.26V, while the voltage of the porous Ni mesh electrode in comparative example 1 increased to 3.35V after running for 240 hours. 2 Coated Fe 3+ / Fe 2+ / Ni 2+ (OH) x The catalytic electrode exhibits higher catalytic activity and long-term stability in water electrolysis than the porous Ni mesh electrode, which increases the service life of the composite catalytic electrode and reduces energy consumption.
[0081] Example 8 A 46-mesh plain nickel mesh was selected as the substrate, and the nickel mesh was sandblasted for 40 minutes using an automatic sandblasting machine, No. 60 corundum, and 15kW power. The corundum particles on the surface were removed by ultrasonic treatment for 1 hour, and then a 0.2 mol / L hydrochloric acid solution was prepared and the sandblasted nickel mesh was etched for 1 hour under ultrasonic conditions (ultrasonic power of 300 W, ultrasonic frequency of 34 KHz, and ultrasonic etching temperature of 30°C), washed with water, and dried to obtain a nickel mesh substrate with a porous surface structure.
[0082] Prepare 0.3 mol / L ferric nitrate and 0.1 mol / L nickel nitrate aqueous solution, add hydrochloric acid stabilizer, the molar ratio of ferric nitrate to hydrochloric acid is 6:1, mix well, and obtain iron-nickel precursor solution. Apply the iron-nickel precursor to the surface of the nickel mesh by dip coating, and after drying in an oven at 60°C, Fe 3+ / Fe 2+ / Ni 2+Compound. Prepare 3.0 mol / L sodium hydroxide and 1.5 mol / L ammonium chloride aqueous solution, and apply the sodium hydroxide and ammonium chloride aqueous solution to the Fe by dip coating. 3+ / Fe 2 + / Ni 2+ On the surface of the compound, after in-situ reaction in an oven at 60°C, Fe 3+ / Fe 2+ / Ni 2+ The hydroxide catalyst layer was treated with ultrasound and water washing twice, and the catalyst layer loading was 2.5-2.8 mg / cm 2 .
[0083] Prepare a uniform slurry of polysulfone (PSF): zirconium oxide (mass ratio) = 100:1, polysulfone and zirconium oxide: NMP (mass ratio) = 4:100, apply it to the surface of the catalyst layer, and then immerse it in deionized water for 48 hours to form a porous composite coating on the surface of the catalyst layer by phase transfer. The composite coating loading is about 0.15mg / cm 2 , Fe coated with porous composite coating was prepared 3+ / Fe 2 + / Ni 2+ The hydroxide composite catalytic electrode, named Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / ZrO 2 -8.
[0084] Performance Test: Test method: A two-chamber electrolytic cell was used, and the anode was the Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / ZrO 2 -8. The porous Ni mesh catalytic electrode prepared in Comparative Example 1, the cathode is a titanium oxide-coated platinum-nickel composite catalytic electrode, the diaphragm is a composite diaphragm, and the electrode working area of the anode and cathode is 10 cm 2 Each composite catalytic electrode was loaded with 3 pieces, and a 6-chamber electrolyzer was used for comparative testing. During the test, a peristaltic pump was used to introduce electrolyte into the electrolyzer. A 30wt% KOH aqueous solution was introduced into the anode and cathode at a flow rate of 150rpm / min, respectively, and the test temperature was 80℃. (1) The test current density was 200mA / cm 2 , 500mA / cm 2 , 1000mA / cm 2 , 1500mA / cm 2 , 2000mA / cm2 (2) Tested at 1500mA / cm 2 240h stability at high current density.
[0085] Test results: When the anode is Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / ZrO 2 -8 (Example 8), the current density is 200mA / cm 2 -2000mA / cm 2 , the voltage for water splitting is between 1.55V and 2.43V, while when the anode is a porous Ni mesh (Comparative Example 1), the voltage for water splitting is between 1.79V and 2.85V, and Fe 3+ / Fe 2+ / Ni 2+ (OH) x @PSF / ZrO 2 -8 has 13.4-14.7% lower energy consumption than porous Ni mesh electrode, and at 1500mA / cm 2 After running for 240 hours at a high current density, the full water splitting voltage can still be maintained at 2.30V, while the voltage of the porous Ni mesh electrode of comparative example 1 increased to 3.35V after running for 240 hours; after a long-term operation test of 1000 hours, the electrolysis voltage can still be maintained at 2.32V. 2 Coated Fe 3+ / Fe 2+ / Ni 2+ (OH) x The catalytic electrode exhibits higher catalytic activity and long-term stability in water electrolysis than the porous Ni mesh electrode, which increases the service life of the composite catalytic electrode and reduces energy consumption.
[0086] It can be understood that the same or similar parts of the above embodiments can be referenced to each other, and the contents not described in detail in some embodiments can refer to the same or similar contents in other embodiments.
[0087] It should be noted that, in the description of the present invention, the terms "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance. In addition, in the description of the present invention, unless otherwise specified, the meaning of "plurality" refers to at least two.
[0088] Any process or method description in a flowchart or otherwise described herein may be understood to represent a module, segment or portion of code that includes one or more executable instructions for implementing the steps of a specific logical function or process, and the scope of the preferred embodiments of the present invention includes alternative implementations in which functions may not be performed in the order shown or discussed, including performing functions in a substantially simultaneous manner or in the reverse order depending on the functions involved, which should be understood by those skilled in the art to which the embodiments of the present invention belong.
[0089] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0090] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A composite catalytic electrode for electrolyzing water and evolving oxygen, characterized in that: include: A porous nickel substrate, a composite catalyst layer and a porous composite bonding layer; The composite catalyst layer is loaded on the porous nickel substrate, and the porous composite bonding layer is coated on the surface of the composite catalyst layer; The composite catalyst layer comprises a nickel-iron-based hydroxide catalyst, and the porous composite bonding layer is a nano-porous polymer ceramic powder composite coating.
2. The composite catalytic electrode for oxygen evolution by water electrolysis according to claim 1, characterized in that: The composite catalyst layer also includes catalyst promoters such as molybdenum, vanadium, manganese or cobalt; The polymer in the nanoporous polymer ceramic powder composite coating is one or more of the alkali-resistant polymers polysulfone or polyethersulfone; The ceramic powder in the nanoporous polymer ceramic powder composite coating is one or more of zirconium oxide, titanium oxide, cerium oxide and niobium oxide.
3. The composite catalytic electrode for oxygen evolution by water electrolysis according to claim 1, characterized in that: The total loading amount of the nickel-iron-based hydroxide catalyst is 0.1-30 mg / cm 2 , the nickel-iron molar ratio is 1:50-2:1; The loading amount of the nanoporous polymer ceramic powder composite coating is 0.01-5 mg / cm 2 The mass ratio of polymer to ceramic powder is 100:1-1:
20.
4. The composite catalytic electrode for oxygen evolution by water electrolysis according to claim 1, characterized in that: The total loading amount of the nickel-iron-based hydroxide catalyst is 0.5-30 mg / cm 2 , the nickel-iron molar ratio is 1:4-1:1; The loading amount of the nanoporous polymer ceramic powder composite coating is 0.1-4 mg / cm 2 The mass ratio of polymer to ceramic powder is 100:1-1:
20.
5. The composite catalytic electrode for oxygen evolution by water electrolysis according to claim 1, characterized in that: The porous nickel substrate is a nickel mesh, a nickel felt, a nickel alloy mesh, a nickel foam or a nickel alloy foam.
6. A method for preparing a composite catalytic electrode for oxygen evolution by electrolysis of water, characterized in that: include: adding a stabilizer to a nickel-iron catalyst precursor compound solution to form a catalyst solution; After coating the catalyst solution on the surface of the porous nickel substrate, the catalyst solution is reacted with an alkaline solution to form a composite catalyst layer; After coating the ceramic powder and the polymer slurry onto the surface of the composite catalyst layer, a protective layer is formed by a phase transfer method.
7. The method for preparing the composite catalytic electrode for oxygen evolution by water electrolysis according to claim 6, characterized in that: The stabilizer is amino acid, hydrochloric acid, sulfuric acid, acetic acid, nitric acid or citric acid; The iron precursor salt in the nickel-iron catalyst precursor compound solution is one or more of ferric chloride, ferric nitrate, ferric sulfate, and ferric acetate; The nickel precursor salt in the nickel-iron catalyst precursor compound solution is one or more of nickel chloride, nickel nitrate, nickel sulfate, and nickel acetate; In the nickel-iron catalyst precursor compound solution, the molar ratio of the nickel-iron precursor to the stabilizer is 1:2-50:
1.
8. The method for preparing the composite catalytic electrode for oxygen evolution by water electrolysis according to claim 6, characterized in that: After coating the catalyst solution onto the surface of the porous nickel substrate, the method further comprises: The porous nickel substrate coated with the catalyst solution is dried and then reacted in situ with an alkaline solution to form a composite catalyst layer.
9. The method for preparing the composite catalytic electrode for oxygen evolution by water electrolysis according to claim 6, characterized in that: The ceramic powder in the ceramic powder and polymer slurry is an oxide or a composite oxide of a metal chemical element; The ceramic powder and the polymer in the polymer slurry are alkali-resistant polymers; The slurry solvent in the ceramic powder and polymer slurry is a solution capable of dissolving the alkali-resistant polymer.
10. A water electrolysis hydrogen evolution device, characterized in that: The electrode of the water electrolysis hydrogen evolution device is a water electrolysis oxygen evolution composite catalytic electrode as claimed in any one of claims 1 to 5.